Study on Evaluation of Locally Made Horizontal Penetrometer to Measure Soil Compaction under Egyptian Conditions - A. A. Meselhy (New Visions in Biological Science Vol. 7, 2021)
Measuring soil penetration resistance is one of the most important measurements that express the soil compaction status. Soil compaction is an important physical limiting factor for the root growth and plant emergence and is one of the major causes for reduced crop yield worldwide, thus determining the type and degree of tillage that suit the soil conditions. Soil compaction can also influence agricultural machinery and implement performances, promoting an expansion in potency demand for traction. The traditional vertical penetrometer is the famous device to measure soil penetration resistance. The data collected by it are not sufficient to characterize the soil compaction status, as there may be a variation in the soil compaction values in one site, which requires taking several measurements to obtain high accuracy in the measurement, which requires a great effort and time. Therefore, the objective of this study was to achieve a more accurate, less effort and faster way to measure soil penetration resistance and generate soil compaction maps for different depth layers of the soil. To do so, a locally made horizontal penetrometer designed and manufactured, which mounted on an agricultural tractor, consisted of a mechanical system and data acquisition system (DAS) tabulate the measured quantities. After that, soil compaction maps could be generated using data collected. The data automatically stratified to determine soil compaction distribution at different layers. The system was successfully tested in field conditions, in Ras-Sudr Research Station, South Sinai, in sandy loam soil where, nine levels of device forward speed with tractor were studied (0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4 and 4.5) km.h-1 and three levels of measurement depth (20, 30 and 40) cm. The soil penetration resistance measurements of the proposed horizontal penetrometer were compared with the traditional vertical penetrometer at the same measurement locations and soil depths, for calibration the horizontal penetrometer and calculation the correction factor at different speeds and measurement depths where, found that horizontal penetrometer reading was greatly affected by their change. A multiple regression equation calculated to determine the horizontal penetrometer reading correction factor by the speed and measurement depth. So, with this equation, the correction factor of horizontal penetrometer readings calculated by knowing both the speed of movement and measurement depth of the penetrometer. Then maps created to describe soil penetration resistance at various depths. Thus, a complete picture of the soil compaction status available by the least time and effort as well as high accuracy. This allows determining the optimum tillage type that used. The horizontal penetrometer evaluated by studying the effect of forward speed of the device’s movement with the tractor on the draft force (kN), fuel consumption rate (l.h-1), fuel consumption per unit area (l.ha-1) and actual field capacity (ha.h-1). The results showed that an increasing percentage in draft force, fuel consumption rate and actual field capacity were about of 197%, 191% and 610%, respectively, with an increasing the forward speed from 0.5 to 4.5 km.h-1. The optimum speed of the horizontal penetrometer, which achieved the lowest fuel consumption per unit area (l.ha-1), was determined to be about of 3.13 km.h-1. It was concluded that the system tested in this study could be used to assess the distribution of compaction at soil different layers, and to create maps that give a visualization of the spatial variation of the compaction distribution in the soil at different depths, from which it is possible to determine the appropriate type and degree of tillage.